2001
DOI: 10.1021/bi010640u
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane-Proximal Tryptophan-Rich Region of the HIV Glycoprotein, gp41, Forms a Well-Defined Helix in Dodecylphosphocholine Micelles,

Abstract: The membrane-proximal tryptophan-rich region of the HIV transmembrane glycoprotein, gp41, plays an important role in the membrane fusion reaction. Using NMR spectroscopy, we have studied the tertiary structure of a synthetic 19-residue amidated peptide (NH2-KWASLWNWFNITNWLWYIK-CONH2) corresponding to this region in membrane-mimetic environments. Initial experiments in sodium dodecyl sulfate/H2O micelles and trifluoroethanol gave poor results, because of low solubility. However, in dodecylphosphocholine micelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
178
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(191 citation statements)
references
References 65 publications
12
178
1
Order By: Relevance
“…To date, few immunogenicity studies focused on the 4E10 epitope have been reported. The extended helical structure of an MPER peptide, KWASLWNWFNITNWLWYIK in DPC micelles was also revealed by an NMR study offering a model of possible interaction of this region with the membrane [45]. More recently, a crystal structure of a 4E10 Fab in complex with a peptide bearing the sequence, WNWFDITNW revealed its major contact residue segment, WFDIT to be in a helical conformation [46].…”
Section: Introductionmentioning
confidence: 93%
“…To date, few immunogenicity studies focused on the 4E10 epitope have been reported. The extended helical structure of an MPER peptide, KWASLWNWFNITNWLWYIK in DPC micelles was also revealed by an NMR study offering a model of possible interaction of this region with the membrane [45]. More recently, a crystal structure of a 4E10 Fab in complex with a peptide bearing the sequence, WNWFDITNW revealed its major contact residue segment, WFDIT to be in a helical conformation [46].…”
Section: Introductionmentioning
confidence: 93%
“…To this aim, we have chosen C34 instead of T20 because the former has more potent antiviral activity in vitro, whereas the latter already includes a hydrophobic C-terminal segment that drives insertion into lipid membranes (32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…The guanidinium group of R has a more dispersed positive charge than the single amine of K, possibly enhancing electrostatic interactions between peptides and the negatively charged bacterial membrane surface (39,53). On the other hand, the bulkier W side chain may ensure more efficient interaction with membrane surfaces, allowing peptides to partition in the bilayer interface, in contrast with other nonpolar side chains such as F, P, or Y (46,56).…”
mentioning
confidence: 99%